Potential Involvement of Obesity-Associated Chronic Inflammation in the Pathogenesis of Idiopathic Spinal Epidural Lipomatosis. Issue 23 (1st December 2016) - Fujita, Nobuyuki; Hosogane, Naobumi; Hikata, Tomohiro; Iwanami, Akio; Watanabe, Kota; Shiono, Yuta; Okada, Eijiro; Ishikawa, Masayuki; Tsuji, Takashi; Shimoda, Masayuki; Horiuchi, Keisuke; Nakamura, Masaya; et al.
Abstract : Study Design: Multicenter case-control study. Objective: To characterize the pathogenesis of idiopathic spinal epidural lipomatosis (SEL). Summary of Background Data: SEL is often associated with the history of steroid use or endocrine disorders; however, the pathogenesis of idiopathic SEL remains poorly understood. Methods: Sixteen patients who underwent lumbar decompression surgery due to severe idiopathic SEL were included in the study (L group, 15 men and 1 woman; mean age, 71.5 yrs). Fifteen patients without SEL, who underwent decompression surgery for lumbar canal stenosis, were selected as controls (C group, 14 men and 1 woman; mean age, 70.3 yrs). The following parameters were analyzed in these two groups: body mass index (BMI), medical history, histology, the size of adipocytes in the epidural fat (EF) tissues, and the expression level of the transcripts for adiponectin, leptin, tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and IL-8. Results: The mean BMI of the L group was significantly higher than that of the C group (29.1 vs. 25.2 kg/m 2, P  = 0.006), and there was a significant correlation between BMI and the width of EF in both groups. The average adipocyte size in the EF was significantly larger in the L group than in the C group (2846.8 vs. 1699.0 μm 2, P  = 0.017). Furthermore, the expression levels of the transcripts for TNF-α and IL-1β in the L group were significantly higher than those in the C group [2.59-fold increase ( P  = 0.023) and 2.60-fold increase ( P  = 0.015), respectively]. Conclusion: Our data suggest that the pathogenesis of idiopathic SEL is associated with obesity. In addition, the increased expression of two major inflammatory cytokines in the EF in the L group may indicate that SEL is causally related to chronic inflammation. Level of Evidence: 3